ADAM10-cleaved ephrin-A5 contributes to prostate cancer metastasis - Chenchen Cai; Miaomiao Zhang; Lei Liu; Haoliang Zhang; Yi Guo; Ting Lan; Yinhai Xu; Ping Ma; Shibao Li (Cell Death and Disease, 2022)
Abstract A disintegrin and metalloprotease-10(ADAM10) promotes the metastasis of prostate cancer (PCa), but the specific mechanism is indistinct. Herein, DU145 cell lines with stable overexpression and knockdown of ADAM10 were constructed. We found that ectopic expression of ADAM10 not only significantly facilitated cell proliferation, migration, invasion, and inhibited apoptosis, but also could specifically hydrolyze ephrin-A5 and release the ephrin-A5 soluble ectodomain into extracellular media in vitro. These effects were reversed by ADAM10 depletion or treatment of GI254023X. Meanwhile, the co-location and physical interaction among EphA3, ephrin-A5, and ADAM10 were observed in PCa cells using immunofluorescence and immunoprecipitation techniques. Interestingly, overexpression of EphA3 exerted opposite effects in DU145 (ephrin-A5 + ) cells and PC-3 (ephrin-A5 ± ) cells. In addition, the pro-tumor function of EphA3 was reversed by the treatment with the exogenous ephrin-A5-Fc, which increased the phosphorylation level of EphA3 in PC-3 (ephrin-A5 ± ) cells. In nude mice, ADAM10 accelerated growth of the primary tumor, decreased the level of ephrin-A5 in the tumor tissue, but increased the level of ephrin-A5 in the peripheral blood, accompanied with an increase in the expression of CD31 and VEGF (vascular endothelial growth factor) in the tissue. What is more, the serum ephrin-A5 content of patients with metastatic PCa was significantly higher than that of the non-metastatic group (P < 0.05). The receiver operating characteristic curve(ROC) showed that the area under the curve(AUC) of serum ephrin-A5 as a marker of PCa metastasis was 0.843, with a sensitivity of 93.5% and a specificity of 75%. It is concluded that ADAM10-mediated ephrin-A5 shedding promotes PCa metastasis via transforming the role of EphA3 from ligand-dependent tumor suppressor to ligand-independent promoter, and ephrin-A5 in the blood can be used as a new biomarker for PCa metastasis.